Revisiting Social Justice: Exploring the Qur’anic Paradigm in Addressing Contemporary Challenges - Junaidi, Juliyana; Abdul Majid, Latifah; Nazri , Mohd Arif (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
Freedom, equality, and fraternity serve as fundamental pillars within discussions on social justice, yet in the contemporary era, these principles have been greatly undermined, leading to increased social injustice within the realms of social, politics and economics. One contributing factor to this phenomenon is the predominant reliance on secular approaches to address social justice issues, neglecting the potential role of divine guidance found in the Qur’an. Despite being a comprehensive reference encompassing principle of social justice, the Qur’an has been largely overlooked as a source for solutions in the modern era. Therefore, this article aims to examine the Qur’anic paradigm of social justice that hold the potential to address the social justice challenges prevalent in the modern generation. This qualitative study employs content analysis as a primary methodology, supplemented by descriptive and thematic analysis to present the gathered data. Initially, social justice issues are identified, followed by an analysis of relevant Qur’anic verses using Qur’anic commentary books and related sources. The findings highlight fifteen Qur’anic verses that are intricately linked to the principles of social justice within the Qur’an, including the dignified ranking of humanity, freedom of humanity, equitable distribution of wealth and opportunities, and the respect for human rights.